MAGGIE’S STRUGGLE IN PLACING HER EXISTENCE AT THE PATRIARCHAL SOCIETY IN THE MILL ON THE FLOSS BY GEORGE ELLIOT - INDRIANI, FRISCA ARUM (LANTERN (Journal on English Language, Culture and Literature), 2013)
Novel The Mill on the Floss is one of George Elliot’s novels that describing the situation and condition of the English society and also representing human life in 1837-1901 century which is called Victorian Era. At the moment, women were dominated by men and considered inferior. The condition is portrayed in this novel because the novel tells about the life of women, especially the life of the main female character, Maggie Tulliver, who is the victim of the standard beauty in her family. It is interesting to analyze this novel because it describes Maggie’s life in her family that is dominated by her parents and her family, and is shacked by the patriarchal society The Mill on the Floss shows how difficult the struggle of women is in placing her existence in the patriarchal society. This final project will show the conflict that Maggie experiences to fight for her existence in the patriarchal society.